Metabolic and inflammatory genes in schizophrenia. Issue 1 (30th January 2015) - Chase, Kayla A.; Rosen, Cherise; Gin, Hannah; Bjorkquist, Olivia; Feiner, Benjamin; Marvin, Robert; Conrin, Sean; Sharma, Rajiv P.
Abstract: Energy metabolism and immunity are characterized as abnormal in schizophrenia. Because these two systems are highly coordinated, we measured expression of prototypic obesogenic and immunogenic genes in freshly harvested PBMC from controls and participants with schizophrenia. We report significant increases in PPARγ, SREBP1, IL-6 and TNFα, and decreases in PPARα and C/EPBα and mRNA levels from patients with schizophrenia, with additional BMI interactions, characterizing dysregulation of genes relating to metabolic-inflammation in schizophrenia. Highlights: Examined both obesogenic and immunogenic gene expression in the same sample. Utilized mRNA from discrete tissue (peripheral lymphocytes) to avoid interpretation from multiple sources. Discovered dysregulated expression of both obesogenic and immunogenic genes in schizophrenia when compared to normal controls.